ANALYSIS OF WORKING CAPITAL. - Collins, George William (The Accounting Review, 1946)
Abstract Working capital is the excess of current assets over current liabilities. Current assets are those assets which will generally be converted into cash within one year in the normal course of business. Current liabilities are those liabilities which will generally be paid during the ensuing year. Working capital may be regarded as a reservoir, the level and content of which is constantly being changed by business transactions. The condition of the reservoir at any particular time is shown by a summary of current assets and current liabilities in this article. To show the flow in and out of the reservoir, it calls for another type of statement covering a period of time and showing the sources from which working capital was obtained, and the purposes for which working capital was used. Changes in debits and credits appearing in a worksheet are frequently net amounts. The primary purpose of reclassifying entries is to set out as a separate item on the worksheet each amount making up the net amount. The information needed to prepare such entries is obtained from analyses of the accounts.